The effect of frailty on survival in patients with COVID-19 (COPE): a multicentre, European, observational cohort study - Jonathan Hewitt, FRCP; Ben Carter, PhD; Arturo Vilches-Moraga, FRCP; Terence J Quinn, FRCP; Philip Braude, MRCP; Alessia Verduri, MD; Lyndsay Pearce, FRCS; Michael Stechman, FRCS; Roxanna Short, PhD; Angeline Price, BSc; Jemima T Collins, MRCP; Eilidh Bruce, MBChB; et al. (Elsevier, 2020)
Summary: Background: The COVID-19 pandemic has placed unprecedented strain on health-care systems. Frailty is being used in clinical decision making for patients with COVID-19, yet the prevalence and effect of frailty in people with COVID-19 is not known. In the COVID-19 in Older PEople (COPE) study we aimed to establish the prevalence of frailty in patients with COVID-19 who were admitted to hospital and investigate its association with mortality and duration of hospital stay. Methods: This was an observational cohort study conducted at ten hospitals in the UK and one in Italy. All adults (≥18 years) admitted to participating hospitals with COVID-19 were included. Patients with incomplete hospital records were excluded. The study analysed routinely generated hospital data for patients with COVID-19. Frailty was assessed by specialist COVID-19 teams using the clinical frailty scale (CFS) and patients were grouped according to their score (1-2=fit; 3-4=vulnerable, but not frail; 5-6=initial signs of frailty but with some degree of independence; and 7-9=severe or very severe frailty). The primary outcome was in-hospital mortality (time from hospital admission to mortality and day-7 mortality). Findings: Between Feb 27, and April 28, 2020, we enrolled 1564 patients with COVID-19. The median age was 74 years (IQR 61-83); 903 (57·7%) were men and 661 (42·3%) were women; 425 (27·2%) had died at data cutoff (April 28, 2020). 772 (49·4%) were classed as frail (CFS 5-8) and 27 (1·7%) were classed as terminally ill (CFS 9). Compared with CFS 1-2, the adjusted hazard ratios for time from hospital admission to death were 1·55 (95% CI 1·00-2·41) for CFS 3-4, 1·83 (1·15-2·91) for CFS 5-6, and 2·39 (1·50-3·81) for CFS 7-9, and adjusted odds ratios for day-7 mortality were 1·22 (95% CI 0·63-2·38) for CFS 3-4, 1·62 (0·81-3·26) for CFS 5-6, and 3·12 (1·56-6·24) for CFS 7-9. Interpretation: In a large population of patients admitted to hospital with COVID-19, disease outcomes were better predicted by frailty than either age or comorbidity. Our results support the use of CFS to inform decision making about medical care in adult patients admitted to hospital with COVID-19. Funding: None.